Impact on the outcome of pharmacotherapy of senior Indian inpatients: A pharmacist led intervention - M, Mandavi; R, Padmavathi; R, Mangu; T, Pramil; K, Vinay (Indian Journal of Pharmacy Practice)
It is well known that due to physiological changes, elderly patients are prone to suffer from Drug-Related Problems (DRPs). By the year 2040, the elderly will account for 14% of total global population. Since the elderly population will increase, it is expected that the DRPs will also increase. To determine the potentially inappropriate prescription(s), understand risk factors and study the impact of providing regular feedback to the clinicians on the inappropriate medications prescribed to the elderly inpatients using the Modified Updated Beers Criteria 2003. A 3 year long term prospective interventional study included 1972 elderly inpatients (60yrs or above) at a public teaching hospital. Regular feedback was provided to the clinicians and the changes effected in the therapy were documented. The average age of the patients was 68.03±0.16 yrs. On an average, each patient had 2 diagnoses & was prescribed 7 drugs. Of 1972 patients, 285 (15%) patients were identified to have at least one inappropriate medication. The most common inappropriate drugs were administration of anticoagulant therapy with aspirin or Clopidogrel (22.2%), Amitriptyline (18.5%), Digoxin (9.8%), Amiodarone (8.7%) and Chlorphenaramine (7.3%), followed by Promethazine & Ferrous Sulfate (4.9%). The risk factors for the inappropriate prescription were age over 70 yrs, more than 5 medications prescribed, longer stay in the hospital and multiple diagnoses. The extent of inappropriateness in the first, second and third year of the study was 19%, 18% and 7%, respectively. There was a significant improvement in the inappropriateness in third year, when compared from the first 2 years of the study. Some illustrative instances where the drug(s) was discontinued or the use decreased, in the third year, are anticoagulant therapy with Aspirin or Clopidogrel (4.6% to 0.46%), Amitriptyline (3.3% to 1.3%), Digoxin (2.1% to Nil), Promethazine (1.05% to Nil), and use of Anticholinergic agents in obstructed bladder (0.52% to Nil). These results have demonstrated that it is possible to reduce inappropriateness of pharmacotherapy in elderly patients through provision of relevant unbiased information to healthcare professionals. Reinforcement of the feedback is a possible route to sustain the improvement.
Keywords: Elderly; Inappropriate drugs; Beers criteria 2003; India